STRATEGI OPTIMALISASI PEMASARAN DIGITALTOKOPILA COFFEE & ROASTERY DI TANJUNG PANDAN BELITUNG - Da Lopez, Viktorianus Mahendra; Razali, Fadilla (Universitas Indraprasta PGRI Jakarta, 2025)
This study aims to analyze the utilization of digital platforms to enhance the marketing of coffee products by Tokopila Coffee & Roastery in Tanjung Pandan, Belitung. A descriptive qualitative method was employed, with data collected through in-depth interviews with five informants (the owner, marketing team, and consumers), as well as observations of Tokopila’s social media and Google reviews. The findings indicate that platforms such as Instagram and TikTok significantly contribute to increasing product visibility, expanding market reach, and fostering customer loyalty. However, challenges remain in managing visual content quality, consumer engagement, and online review handling. It is concluded that Tokopila should further optimize its digital marketing strategy by improving content quality, customer service, SEO implementation through hashtags and captions, leveraging social media analytics, and expanding to other platforms such as YouTube and Facebook.